The missing corpse eaudiobook - Bannalec, Jean-Luc (Commissaire Dupin, 2019)
The Missing Corpse is internationally bestselling author Jean-Luc Bannalec's fourth novel in the Brittany Mystery series. It's picturesque, suspenseful, and the next best thing to a trip to Brittany. Along the picturesque Belon River, home of the world famous oyster beds, between steep cliffs, ominous forests and the Atlantic Ocean, a stubborn elderly film actress discovers a corpse. By the time Commissaire Dupin arrives at the scene, the body has disappeared. A little while later, he receives a phone call from the mystical hills of Monts d'Arree, where legends of fairies and the devil abound: another unidentified body has turned up. Dupin quickly realizes this may be his most difficult and confounding case yet, with links to celtic myths, a sand theft operation, and mysterious ancient druid cults.